Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy. Issue 1 (December 2018) - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay; Rajamohanan, P.; Reddy, D.; Shanmugam, Dhanasekaran
Abstract Glucose is an essential nutrient forPlasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show thatP. falciparum infected erythrocytes consume ~20 times more glucose, and trophozoites metabolize ~6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.